Ode to Oseltamivir and Amantadine?. Issue 1 (1st February 2006) - Conly, JM; Johnston, BL
Abstract : Influenza A and B viruses are the two major types of influenza viruses that cause human epidemic disease. Influenza A viruses are further categorized into subtypes based on two surface antigens: hemagglutinin (H) and neuraminidase (N). Influenza B viruses are not categorized into subtypes (1). Influenza A viruses are found in many animal species, including humans, ducks, chickens, pigs, whales, horses and seals, whereas influenza B viruses circulate only among humans. The H antigen contains common and strain-specific antigens, demonstrates antigenic variation, and acts as a site of attachment of the virus to host cells to initiate infection (1). The N antigen contains subtype-specific antigens and also demonstrates antigenic variation between subtypes. It is a surface glycoprotein possessing enzymatic activity essential for viral replication in both influenza A and B viruses. The N antigen allows the release of newly produced virions from infected host cells, prevents the formation of viral aggregates after release from the host cells, and prevents viral inactivation by respiratory mucous (2, 3). It is thought that this enzyme may also promote viral penetration into respiratory epithelial cells and may contribute to the pathogenicity of the virus by promoting production of proinflammatory cytokines such as interleukin-1 and tumour necrosis factor from macrophages (4-6).